2020
DOI: 10.1145/3432217
|View full text |Cite
|
Sign up to set email alerts
|

BlinKey

Abstract: Virtual Reality (VR) has shown promising potentials in many applications, such as e-business, healthcare, and social networking. Rich information regarding user's activities and their online accounts is stored in VR devices. If it is carelessly unattended, then attackers, including insiders, can make use of the stored information to, for example, perform in-app purchases at the legitimate owner's expenses. Current solutions, mostly following schemes designed for general personal devices, have been proved vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In [176], Zhu et al proposed BlinKey, a two-factor VR authentication scheme based on the user's blinks as a password and pupil size as a biometric trait. They investigated the accuracy of BlinKey through extensive evaluations using four different ML classifiers and concluded that the k-NN classifier achieved the best results with a 0.04% EER and the shortest training time.…”
Section: Multifactor and Multimodal Authenticationmentioning
confidence: 99%
“…In [176], Zhu et al proposed BlinKey, a two-factor VR authentication scheme based on the user's blinks as a password and pupil size as a biometric trait. They investigated the accuracy of BlinKey through extensive evaluations using four different ML classifiers and concluded that the k-NN classifier achieved the best results with a 0.04% EER and the shortest training time.…”
Section: Multifactor and Multimodal Authenticationmentioning
confidence: 99%
“…There exists a reciprocal relationship between usability and security [49]. When security is prioritized, usability may suffer.…”
Section: Usabilitymentioning
confidence: 99%
“…In 2009, Hansen et al [17] reviewed gaze-based studies from the past 30 years and proposed that gaze features have unique characteristics that could be utilized for authentication. Eye movements, blinking, velocity, and other behaviors are distinctive [11,28,41,49] and can be used successfully to authenticate users. However, these biometric features demand a high cognitive load and are less user-friendly.…”
Section: Authentication In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is Blinkey [116] because it employs two-factor authentication using both knowledge-based and biometrics. The biometric feature involves creating a password based on the user's blink pattern which can be stimulated by a music rhythm.…”
Section: Authenticationmentioning
confidence: 99%